Capabilities of the Modern Leader in the Management Process - Kuzieva Gulnoza Makhamadalievna (Periodica Journal, 2022)
This article provides complete information about the formation of the management ability of a modern leader, directions for the development of necessary skills, qualifications and skills in managing employees, requirements for a modern leader, leadership styles, types.
Keywords: employee; management; idea; direction